Synthesis and characterization of poly (D,L-lactide-co-ε-caprolactone) for application in tendon/ligament tissue engineering / Wahida Abdul Rahman, Jean-Luc Six and Cécile Nouvel - Abdul Rahman, Wahida; Six, Jean-Luc; Nouvel, Cécile (Universiti Teknologi MARA, Perlis, 2012)
In this research, copolymers of poly (D,L-lactide-co-ε-caprolactone) (PLCL) with 50:50 feed ratio were synthesized by the coordination-insertion ring opening polymerization (ROP) of cyclic esters at different temperature (130 0C, 150 0C and 200 0C). Both Sn(II)octoate (SnOct2) and isopropanol (iPrOH) were used as catalyst and initiator respectively and polymerization reaction were took part from 24 hours until 1 week. The conversion of monomer D,L-lactide and ε-caprolactone, polydispersity index (PDI) and total average molecular weight of copolymer PLCL can be determined by proton nuclear magnetic resonance (1H-NMR) and size exclusion chromatography coupled multi-angle laser light scattering (SEC-MALLS). Both analyses showed the increasing trend as the reaction temperature increased. The average sequence lengths of the lactidyl units (leLL) and caproyl (lecap) units, the degree of randomness (R) and the transesterification coefficients (TI and TII) were calculated from the 13C-NMR spectra. The average sequence lengths showed the decreasing trends, meanwhile there were small significant value increased for degree of randomness and transesterification coefficients when reaction temperature increased from 130 0C to 200 0C. The fabricated PLCL copolymers have a potential to be transformed into three dimensional scaffold for application in tendon/ligament tissue engineering.